Glutathione‐dependent denitrosation of GSNOR1 promotes oxidative signalling downstream of H2O2. (11th February 2020) - Zhang, Tianru; Ma, Mingyue; Chen, Tao; Zhang, Linlin; Fan, Lingling; Zhang, Wei; Wei, Bo; Li, Shengchun; Xuan, Wei; Noctor, Graham; Han, Yi
Abstract: Photorespiratory hydrogen peroxide (H2 O2 ) plays key roles in pathogenesis responses by triggering the salicylic acid (SA) pathway in Arabidopsis. However, factors linking intracellular H2 O2 to activation of the SA pathway remain elusive. In this work, the catalase‐deficient Arabidopsis mutant, cat2, was exploited to elucidate the impact of S ‐nitrosoglutathione reductase 1 (GSNOR1) on H2 O2 ‐dependent signalling pathways. Introducing the gsnor1‐3 mutation into the cat2 background increased S ‐nitrosothiol levels and abolished cat2 ‐triggered cell death, SA accumulation, and associated gene expression but had little additional effect on the major components of the ascorbate‐glutathione system or glycolate oxidase activities. Differential transcriptome profiles between gsnor1‐3 and cat2 gsnor1‐3 together with damped ROS‐triggered gene expression in cat2 gsnor1‐3 further indicated that GSNOR1 acts to mediate the SA pathway downstream of H2 O2 . Up‐regulation of GSNOR activity was compromised in cat2 cad2 and cat2 pad2 mutants in which glutathione accumulation was genetically prevented. Experiments with purified recombinant GSNOR revealed that the enzyme is posttranslationally regulated by direct denitrosation in a glutathione‐dependent manner. Together, our findings identify GSNOR1‐controlled nitrosation as a key factor in activation of the SA pathway by H2 O2 and reveal that glutathione is required to maintain this biological function. Abstract : The present study investigates the roles of GSNOR and glutathione in regulating the SA pathway triggered by photorespiratory H2 O2 in Arabidopsis. Up‐regulation of GSNOR is required for the activation of SA pathway downstream of H2 O2 . Glutathione‐dependent denitrosation is necessary to maintain the up‐regulation of GSNOR activities and may coordinate GSNOR activities with protein SNO levels to ensure appropriate signalling strength through the SA pathway in response to H2 O2 .